Implementasi Perubahan Kebijakan dan Peraturan Impor Tas Terhadap Produk Lokal, Studi Kasus di Indonesia - Irna Yaumil Isni; Zulkarnain; Septiawan, Bambang (Universitas Islam Balitar, 2025)
This study aims to analyze the impact of policy changes and regulations on bag imports on the local product industry in Indonesia. In recent years, the Indonesian government has adjusted import regulations to protect domestic producers from the influx of cheaper and more abundant foreign goods. This case study highlights how these policies are implemented, the challenges faced in their implementation, and their impact on local bag producers, including business growth, competitiveness, and consumer preferences. The research method used is descriptive qualitative with a case study approach in several local bag production centers in Indonesia, such as Tasikmalaya and Bandung. The research findings indicate that while the policy provides protection for the domestic market, its implementation still faces bureaucratic obstacles, insufficient policy outreach, and limited support for enhancing local production capacity. This study recommends the need for synergy between trade policies and local industry empowerment to create a healthy and sustainable ecosystem for domestic products.